Differential Regulation of Morphology and Estrogen Receptor-Alpha Expression in the Vagina of Ovariectomized Adult Virgin Rats by Estrogen Replacement: A Histological Study - Ting Li; Yuanyuan Ma; Hong Zhang; Ping Yan; Lili Huo; Yongyan Hu; Xi Chen; Ting Li; Miao Zhang; Zhaohui Liu (International Journal of Endocrinology)
Background. To determine the exact role of estrogen in vaginal tissue morphology and estrogen receptor-alpha (ERα) distribution in the vagina, which remains controversial. Methods. Sixty rats were randomly categorized: sham-operated (sham), ovariectomy (OVX), and four estradiol treatments (estradiol valerate at 0.4, 0.8, 1.6, and 3.2 mg/kg/day) for 2 weeks. Thereafter, vaginal samples were biopsied from the distal- and proximal-half portions. The percentage of ERα-immunoreactive cells and the ERα score were quantified using immunohistochemistry to assess changes in ERα expression and distribution. Results. OVX induced significant vaginal atrophy and organic index. Estrogen-replacement therapy (ERT) reversed vaginal atrophy. The vaginal distal-half areas showed lower ERα% than the proximal-half areas. The ERα% increased sharply 4 weeks after OVX, especially in the epithelial layer (P=0.023). ERT elicited different degrees of reductions in tissues after the 2-week treatment, but the ERα% in only the epithelium recovered in parallel with that in the sham group (P=0.001). The OVX group showed higher ERα histological scores than the sham group, and the distal-half area changed more evidently than the proximal-half area. ERα expression was nearly unchanged after ERT (P>0.05). Conclusions. ERT is effective for treating obesity and vulvovaginal atrophy caused by hypoestrogenism and advancing age in menopausal women but cannot recover the distribution and expression of ERα.